2011
DOI: 10.1186/1556-276x-6-189
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between structural changes, hydrogen content and annealing in stacks of ultrathin Si/Ge amorphous layers

Abstract: Hydrogenated multilayers (MLs) of a-Si/a-Ge have been analysed to establish the reasons of H release during annealing that has been seen to bring about structural modifications even up to well-detectable surface degradation. Analyses carried out on single layers of a-Si and a-Ge show that H is released from its bond to the host lattice atom and that it escapes from the layer much more efficiently in a-Ge than in a-Si because of the smaller binding energy of the H-Ge bond and probably of a greater weakness of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…It is then argued that the blisters grow from such voids by accumulation of molecular H 2 that had formed by reaction between H atoms released from the (Si-H) n clusters and (Si-H 2 ) n ( n ≥ 1) polymers. The results reported here support and confirm our previous hypothesis that ascribed the blisters in a-Si/a-Ge multilayers to the formation of bubbles containing molecular H 2 [19,20]. …”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…It is then argued that the blisters grow from such voids by accumulation of molecular H 2 that had formed by reaction between H atoms released from the (Si-H) n clusters and (Si-H 2 ) n ( n ≥ 1) polymers. The results reported here support and confirm our previous hypothesis that ascribed the blisters in a-Si/a-Ge multilayers to the formation of bubbles containing molecular H 2 [19,20]. …”
Section: Introductionsupporting
confidence: 92%
“…This work is a contribution in the field of the relationship between H content, H bonding configuration and voids in hydrogenated a-Si single layers deposited by radio frequency (RF) sputtering and subsequently annealed. It was prompted by the need to improve understanding of our previous results about the presence of blisters in hydrogenated a-Si/a-Ge multilayers sputtered in the same way and submitted to annealing with the aim to produce the a-SiGe alloy by Si and Ge diffusion and intermixing [19,20]. It is reported here that annealing of the single a-Si layers causes the voids to grow to such a size to form surface blisters detectable by AFM (atomic force microscopy).…”
Section: Introductionmentioning
confidence: 99%
“…It can thus be assumed that the annealed hydrogenated samples do not change significantly their intrinsic strain status with respect to that of the as-deposited ones. Stress measurements in samples grown and annealed under the same conditions as here are given in Frigeri et al (2011).…”
Section: Resultsmentioning
confidence: 99%
“…Blistering has been observed as a result of hydrogen absorption by magnetic Co/Pd MLs [6]; blisters and craters formed during annealing of hydrogenated Si-Ge ML structures related to multi-junction solar cells technology [7]; hydrogen ion irradiation induced blistering of Mo/Si MLs designed for solar missions [8]. It has been shown that hydrogen-induced blistering of Mo/Si MLs can have a strong dependence on the precise composition of the incident flux [9].…”
Section: Introductionmentioning
confidence: 99%